Investigating Task Understanding in Online Repositories Equipped with Topic Map Indexes: Implications for Improving Self-Regulatory Processes in Graduate Learners - Venkatesh, Vivek; Shaikh, Kamran (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education, 2008)
AbstractTheories of cognitive information retrieval can work in concert with those of educational psychology to better formalize self-regulatory processes, such as task understanding, in online learning. Results from a prior statistical exploration of 38 graduate learners using a topic map (ISO 13250) index to browse an online repository of instructor-annotated essays in order to complete an ill-structured essay task indicate improved performance and task understanding. This follow-up study analyzes the inductive content of interviews and computer-based user traces for a theoretical sample of 12 of these 38 learners, showing how the semantic nature of the topic map enabled them to pursue distinct paths to browse essays according to individual task understanding and information need.